Kekuatan Hukum Informed Consent Dalam Praktek Euthanasia Di Indonesia - Atriani, Dewi; Yulianto, Ade Yusuf (Fakultas Hukum Universitas Mulawarman, 2023)
The existence of informed consent is a stronghold for doctors to act calmly after the permission of the patient or the patient's family, while euthanasia is defined as the act of